Methionine catabolism in Saccharomyces cerevisiae - Perpète, Philippe; Duthoit, Olivier; De Maeyer, Simon; Imray, Louise; Lawton, Andrew I.; Stavropoulos, Konstantinos E.; Gitonga, Virginia W.; Hewlins, Michael J. E.; Richard Dickinson, J. (FEMS yeast research, 2006)
Abstract The catabolism of methionine to methionol and methanethiol in Saccharomyces cerevisiae was studied using 13C NMR spectroscopy, GC-MS, enzyme assays and a number of mutants. Methionine is first transaminated to α-keto-γ-(methylthio)butyrate. Methionol is formed by a decarboxylation reaction, which yields methional, followed by reduction. The decarboxylation is effected specifically by Ydr380wp. Methanethiol is formed from both methionine and α-keto-γ-(methylthio)butyrate by a demethiolase activity. In all except one strain examined, demethiolase was induced by the presence of methionine in the growth medium. This pathway results in the production of α-ketobutyrate, a carbon skeleton, which can be re-utilized. Hence, methionine catabolism is more complex and economical than the other amino acid catabolic pathways in yeast, which use the Ehrlich pathway and result solely in the formation of a fusel alcohol.